Composite slurry and preparation method thereof, positive plate, battery and power-related equipment
By baking lithium manganese iron phosphate particles and combining graphene and carbon nanotubes to prepare composite slurry, the problems of poor conductivity and low compaction density of lithium manganese iron phosphate materials are solved, and lithium-ion batteries are significantly improved cycling and conductivity.
Patent Information
- Application Number
- CN202411460884.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-10
AI Technical Summary
The problems of poor conductivity, low compaction density and low cycle times of lithium manganese ferrophosphate materials have limited application in lithium-ion batteries, especially due to poor conductivity and increased cost caused by manganese elements.
By baking pre-treatment of lithium manganese iron phosphate particles, combining graphene particles and carbon nanotubes, composite slurry is prepared, material dispersion and fluidity are optimized, and battery performance is improved.
It significantly improves the dispersion and fluidity of the composite slurry, improves the cycling and conductive properties of the battery, reduces moisture residues, and meets the performance needs of lithium-ion batteries.
Smart Images

Figure CN119297248A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a composite slurry and a preparation method thereof, a positive electrode sheet, a battery and electrical equipment. Background Art
[0002] In recent years, lithium manganese iron phosphate materials have attracted extensive research and application due to their higher voltage platform, relatively high energy density, and large cost space. However, the application of lithium manganese iron phosphate materials is limited to poor conductivity, low compaction density, and low number of cycles. Among them, the main reason for the poor conductivity is that the presence of manganese makes it more difficult for lithium ions to be deintercalated and moved, resulting in poor conductivity. The conductivity of lithium iron phosphate is 10-9S / cm, the conductivity of ternary materials is 10-3S / cm, and the conductivity of lithium manganese iron phosphate is 10-13S / cm, which is an order of magnitude different from that of lithium iron phosphate materials, affecting its capacity and rate performance. The reasons for the low compaction density are: in order to improve the conductivity of lithium manganese iron phosphate materials, they are usually modified by reducing particle size and carbon coating, which affects the compaction density. Too small a primary particle size will result in too high a specific surface area, and a large amount of binder and conductive agent are required when preparing battery pole pieces, which will also increase costs. The reasons for the low number of cycles are: the manganese ions in the lithium manganese iron phosphate material have the Jan-Taylor effect, the Mn-O bond undergoes drastic structural changes, which affects the electrochemical cycle performance, and also causes manganese to undergo a disproportionation reaction, causing part of the manganese to dissolve in the electrolyte in the form of Mn2+. At the same time, lithium manganese iron phosphate will undergo a certain degree of particle breakage during the electrode pressing process, which is easy to react with HF in the electrolyte, causing manganese to dissolve and lead to capacity decay. The normal temperature cycle number of a general lithium manganese iron phosphate battery is about 2,000 times, while the cycle number of lithium iron phosphate materials used for energy storage exceeds 6,000 times, and the high-temperature cycle is currently reported to be maintained at around 1,200 times, which limits its application scenarios.
[0003] In order to promote the application of lithium iron manganese phosphate materials, in terms of improving electrochemical performance, researchers have optimized the synthesis method and modified the materials, that is, introduced appropriate amounts of additives or doping elements to improve its electrochemical performance, including capacity, cycle life, charge and discharge rate and stability. In terms of structural optimization, structural optimization is carried out by studying the crystal structure of lithium iron manganese phosphate materials and their relationship with battery performance. For example, by controlling the size, shape and exposure of specific crystal faces of lithium iron manganese phosphate particles, its electrochemical performance can be improved. In the exploration of new lithium iron manganese phosphate materials, some new lithium iron manganese phosphate materials, such as two-dimensional materials, nanomaterials and porous materials, have also been explored and synthesized to further improve the electrochemical performance and application potential of the materials. In terms of battery design and preparation process optimization, improving the formulation of the electrolyte, optimizing the porous electrode structure of the battery and performing interface treatment can also improve the performance of lithium-ion batteries.
[0004] In the preparation process of lithium iron manganese phosphate slurry, in order to improve the gram capacity of lithium iron manganese phosphate material itself, the particle size of the material is usually at a small level, and the specific surface area of the material is usually 15m2 / g-22m2 / g. The higher specific surface area makes it easy for water to contact with the hydrophilic Li phase on the surface of the material, and it is not easy to be removed after being combined with the positive electrode slurry; and the higher viscosity of the slurry affects the uniformity of material dispersion, and the adhesion of small particles makes the slurry fluidity worse, affecting the consistency of the surface density of the pole piece during coating and the performance of chemical film formation. At present, the carbon coating method is often used to improve the surface state of lithium iron manganese phosphate particles. In practical applications, the basic method is to control the moisture content by general means such as controlling the environmental humidity and sealing. In terms of the uniformity of material dispersion and the fluidity of the slurry, the common method is to extend the stirring and dispersing time and use the addition of a strong polar dispersant to improve the slurry state. The disadvantages are that it increases the cost and has limited effect. The additional additives generally increase the internal resistance of the battery and have a certain impact on the battery performance.
[0005] Based on this, it is necessary to research and develop a new formula and preparation process for the preparation of lithium manganese iron phosphate slurry in order to improve the fluidity of the slurry and reduce the residual moisture in the electrode. Summary of the invention
[0006] The first object of the present invention is to provide a composite slurry and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. The composite slurry reduces the presence of water in the slurry, optimizes the uniformity of material dispersion, and improves the fluidity of the slurry, thereby meeting the performance improvement requirements of the prepared positive electrode sheet and lithium-ion battery.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] In a first aspect, the present invention provides a method for preparing a composite slurry, comprising:
[0009] S1, performing a pre-baking treatment on lithium iron manganese phosphate particles to obtain a multi-element precursor material;
[0010] S2, mixing the multi-element precursor material with graphene particles and carbon nanotubes to prepare a composite slurry;
[0011] Wherein, the particle size D of the graphene particles 50 is the particle size D of the lithium manganese iron phosphate particles 50 1.2 to 5 times of.
[0012] In an optional embodiment, the pre-baking treatment in step S1 includes at least one of the following methods:
[0013] Method A: directly baking the lithium manganese iron phosphate particles to obtain the multi-element precursor material;
[0014] Method B: mixing the lithium manganese iron phosphate particles with a binder, and then baking to obtain the multi-element precursor material;
[0015] Preferably, the baking comprises: raising the temperature to a heat treatment temperature under a protective gas atmosphere, and continuing the baking for 4 hours to 36 hours;
[0016] Preferably, after the baking, the moisture content in the multi-component precursor material is less than 1500 ppm;
[0017] Preferably, the heat treatment temperature is lower than the thermal decomposition temperature of the binder;
[0018] Preferably, the heat treatment temperature is ≥88°C;
[0019] Preferably, the protective gas includes at least one of nitrogen, helium and hydrogen;
[0020] Preferably, the step S2 comprises:
[0021] S21, mixing graphene particles and carbon nanotubes to obtain a raw material mixture;
[0022] S22, if the pre-baking treatment adopts method A, a conductive agent and a binder are mixed to form an auxiliary material mixture, and the raw material mixture and the auxiliary material mixture are mixed and then mixed with the multi-component mixture for slurry processing to obtain the composite slurry;
[0023] If the pre-baking treatment adopts method B, the multi-component mixture is sequentially mixed with the conductive agent and the raw material mixture, and mixed and slurried, or the multi-component mixture, the raw material mixture and the conductive agent are mixed together and mixed and slurried to obtain the composite slurry;
[0024] Preferably, the particle size D of the lithium manganese iron phosphate particles is 50 0.3μm~5μm;
[0025] Preferably, the diameter of the carbon nanotube is ≤50nm;
[0026] Preferably, the carbon nanotube has a tube length of ≤100 μm;
[0027] Preferably, the particle size D50 of the binder is 0.1 μm to 60 μm;
[0028] Preferably, the particle size of the graphene particles is ≤3 μm;
[0029] Preferably, the chemical formula of the lithium iron manganese phosphate particles is LiMn 1-x Fe xPO4, where x = 0.05 to 0.95;
[0030] Preferably, the mass ratio of the graphene particles to the carbon nanotubes is 1 / 4 to 7 / 3;
[0031] Preferably, the binder comprises polyvinylidene fluoride and / or polyacrylate;
[0032] Preferably, the conductive agent includes at least one of graphite, acetylene black, conductive carbon black and conductive fiber.
[0033] In an optional embodiment, the step S2, mixing the multi-element precursor material with graphene particles and carbon nanotubes, further comprises adding an organic solvent;
[0034] And / or, the method B adopted for the pre-baking treatment further comprises adding the organic solvent;
[0035] And / or, in step S22, if the pre-baking treatment adopts method A, the process of forming the auxiliary material mixture by mixing the conductive agent and the binder also includes adding a solid active material;
[0036] And / or, in step S22, if the pre-baking treatment adopts method B, the multi-component precursor material is sequentially mixed with the conductive agent and the raw material mixture to prepare a slurry, or the multi-component precursor material, the raw material mixture and the conductive agent are mixed together and the slurry is prepared, and the solid active material is also added;
[0037] Preferably, the solid active material includes at least one of a lithium manganese oxide material, a ternary material, a lithium manganese-rich material and a lithium iron phosphate material;
[0038] Preferably, the organic solvent comprises at least one of N-methyl-2-pyrrolidone, dimethyl carbonate, diethylene carbonate and ethylene carbonate;
[0039] The solid raw materials for preparing the composite slurry include the following components in parts by weight:
[0040] The lithium manganese iron phosphate particles are 20 to 97;
[0041] The binders 1 to 5;
[0042] The conductive agents 1 to 3;
[0043] Raw material mixture 0.5~2;
[0044] Solid active material 0~77.
[0045] In an optional embodiment, the step S21, mixing graphene particles and carbon nanotubes to obtain a raw material mixture, comprises:
[0046] Dispersing the graphene particles in the organic solvent to obtain graphene slurry; dispersing the carbon nanotubes in the organic solvent to obtain carbon nanotube slurry; mixing the graphene slurry and the carbon nanotube slurry to obtain the raw material mixture;
[0047] Alternatively, the graphene particles and the carbon nanotubes are dispersed in the solvent to obtain the raw material mixture.
[0048] In an optional embodiment, in step S22, the conductive agent and the binder are mixed to form an auxiliary material mixture, including:
[0049] Dissolving the binder in the solvent to obtain a glue solution; adding the conductive agent to the glue solution, stirring and mixing, to obtain the auxiliary material mixture;
[0050] In the step S22, the mixed pulping process includes:
[0051] After the materials are mixed, the overall viscosity of the slurry is adjusted using the organic solvent until the viscosity reaches the coating requirement, thereby obtaining the composite slurry.
[0052] In an optional embodiment, at least one of the following mixing treatments is dry mixing:
[0053] A. In step S22, the pre-baking treatment adopts method B, that is, the multi-element precursor material is sequentially mixed with the conductive agent and the raw material mixture;
[0054] B. In step S22, the pre-baking treatment adopts method B, which is a treatment method of mixing the multi-component precursor material, the raw material mixture and the conductive agent together;
[0055] C. In the method B of the pre-baking treatment in step S1, the lithium manganese iron phosphate particles are mixed with a binder;
[0056] Preferably, the dry mixing process is:
[0057] The mixture was stirred in a planetary mixer at a rotation speed of 500 rpm to 1200 rpm and a revolution speed of 10 rpm to 30 rpm for 30 min to 120 min.
[0058] In a second aspect, the present invention provides a composite slurry prepared by the method for preparing the composite slurry described in any one of the aforementioned embodiments.
[0059] In a third aspect, the present invention provides a positive electrode sheet, which is prepared by using the composite slurry described in the aforementioned embodiment.
[0060] In a fourth aspect, the present invention provides a battery, comprising the positive electrode sheet described in the aforementioned embodiment.
[0061] In a fifth aspect, the present invention provides an electrical device, characterized in that it includes a battery as described in the above embodiment.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] In the preparation method of lithium manganese iron phosphate composite slurry of the present application, when the solid raw materials are mixed, a baking pre-treatment is first performed, which can realize the control of moisture in advance and improve the water absorption rate problem; the use of graphene particles and carbon nanotubes can make the solid particles in the composite slurry dispersed evenly. Among them, in addition to being used as a conductive agent in the slurry preparation process, the graphene particles have a particle size D 50 It is 1.2 to 5 times the D50 particle size of lithium manganese iron phosphate particles. In addition, the graphene structure has the effects of lubrication, isolation and hydrophobicity on local lithium manganese iron phosphate particles, and achieves significant improvements in the dispersion and fluidity of the slurry through steric hindrance, thereby optimizing the quality of porous electrode film formation and improving the battery's cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0065] Figure 1 This is a schematic flow chart of a wet mixing method for lithium iron manganese phosphate composite slurry according to Example 1 of the present application;
[0066] Figure 2 This is a schematic flow chart of a semi-dry mixing method for lithium iron manganese phosphate composite slurry according to Example 4 of the present application;
[0067] Figure 3 This is a schematic flow chart of a dry mixing method for lithium iron manganese phosphate composite slurry according to Example 5 of the present application;
[0068] Figure 4 The cycle performance of the positive electrode sheets prepared in the embodiments and comparative examples of the present application in lithium-ion batteries. DETAILED DESCRIPTION
[0069] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0070] In an embodiment of the present application, a method for preparing a composite slurry is provided, and the preparation may include wet mixing, semi-dry mixing or dry mixing.
[0071] Specifically, it may include:
[0072] S1, performing a pre-baking treatment on lithium iron manganese phosphate particles to obtain a multi-element precursor material;
[0073] S2, mixing the multi-element precursor material with graphene particles and carbon nanotubes to prepare a composite slurry;
[0074] Wherein, the particle size D of the graphene particles 50 is the particle size D of the lithium manganese iron phosphate particles 50 For example, it can be 1.2 times, 1.5 times, 2 times, 3 times, 4 times, 5 times, or any value between 1.2 times and 5 times.
[0075] In an optional embodiment, the pre-baking treatment in step S1 includes at least one of the following methods:
[0076] Method A: directly baking the lithium manganese iron phosphate particles to obtain the multi-element precursor material;
[0077] Method B: mixing the lithium manganese iron phosphate particles with a binder, and then baking to obtain the multi-element precursor material;
[0078] In one embodiment of the present application, the baking comprises: raising the temperature to a heat treatment temperature under a protective gas atmosphere, and continuing the baking for 4 hours to 36 hours;
[0079] In one embodiment of the present application, after the baking, the moisture content in the multi-component precursor material is less than 1500 ppm.
[0080] The baking in the three preparation methods of the wet method, the semi-dry method and the dry method comprises: raising the temperature to the heat treatment temperature under a protective gas atmosphere, and continuing the baking for 4h-36h.
[0081] It should be noted that the heat treatment temperature after heating needs to be lower than the thermal decomposition temperature of the binder particles to prevent the binder from being decomposed by heat and affecting the uniformity of the mixed powder. The introduction of protective gas can greatly reduce the introduction of environmental moisture and ensure that the moisture content of the baked solid powder is controlled at a low level.
[0082] In one embodiment of the present application, the heat treatment temperature is lower than the thermal decomposition temperature of the binder;
[0083] In one embodiment of the present application, the heat treatment temperature is ≥88°C; for example, it can be 90°C, 110°C, 160°C, etc., and is an optional temperature lower than the thermal decomposition temperature of the binder.
[0084] In one embodiment of the present application, in a semi-dry mixing method, lithium manganese iron phosphate particles and a binder are mixed and baked to obtain a multi-component precursor material. Before the multi-component precursor material is mixed with the conductive agent, it can also include: before or during the mixing process, the raw materials are transported to a mixing device under a protective gas atmosphere.
[0085] Specifically, the multi-component precursor material obtained after baking is cooled to room temperature and then transported to a stirring device through a loose pipe containing a protective gas. The solid conductive agent and other solid active materials are also transported to the stirring device through a loose pipe containing a protective gas. The stirring device can be a planetary mixer.
[0086] Similarly, in the dry mixing method, before mixing all the materials, the method may further include: conveying the materials to the mixing equipment under an atmosphere of protective gas.
[0087] In one embodiment of the present application, the protective gas includes at least one of nitrogen, helium, and hydrogen;
[0088] In one embodiment of the present application, step S2 includes:
[0089] S21, mixing graphene particles and carbon nanotubes to obtain a raw material mixture;
[0090] S22, if the pre-baking treatment adopts method A, a conductive agent and a binder are mixed to form an auxiliary material mixture, and the raw material mixture and the auxiliary material mixture are mixed and then mixed with the multi-component mixture for slurry processing to obtain the composite slurry;
[0091] If the pre-baking treatment adopts method B, the multi-component mixture is sequentially mixed with the conductive agent and the raw material mixture, and mixed and slurried, or the multi-component mixture, the raw material mixture and the conductive agent are mixed together and mixed and slurried to obtain the composite slurry;
[0092] It can be seen from the above method that the preparation method provided in the embodiments of the present application may include the following:
[0093] (1) The first is a wet mixing method, comprising: mixing raw materials including graphene and carbon nanotubes to obtain a suspension of the raw material mixture; mixing raw materials including a binder and a conductive agent to obtain an auxiliary material mixture (glue); mixing the suspension of the raw material mixture with the auxiliary material mixture, and then mixing and slurrying with a multi-component precursor material (pre-baking treatment using method A) to obtain the lithium manganese iron phosphate composite slurry.
[0094] (2) The second method is a semi-dry mixing method, which includes: mixing raw materials including graphene and carbon nanotubes to obtain a suspension of the raw material mixture; mixing and baking lithium iron manganese phosphate particles with a binder to obtain a multi-component precursor material (method B is used for pre-baking treatment); mixing raw materials including the multi-component precursor material and a conductive agent; and then adding the suspension of the raw material mixture for mixed slurry treatment to obtain the lithium iron manganese phosphate composite slurry.
[0095] (3) The third method is a dry mixing method, which includes: mixing and slurrying raw materials including a multi-component precursor material (pre-baking treatment adopts method B), a conductive agent, graphene particles, and carbon nanotubes to obtain the lithium manganese iron phosphate composite slurry.
[0096] In one embodiment of the present application, the particle size D of the lithium manganese iron phosphate particles is 50 It is 0.3μm to 5μm; for example, it can be 0.5μm, 1μm, 2μm, 3μm or any value between 0.5μm and 3μm.
[0097] In one embodiment of the present application, the diameter of the carbon nanotube is ≤50nm;
[0098] In one embodiment of the present application, the length of the carbon nanotube is ≤100 μm;
[0099] In one embodiment of the present application, the particle size D50 of the binder is 0.1 μm to 60 μm; for example, it can be 0.1 μm, 0.5 μm, 1 μm, 10 μm, 20 μm, 30 μm, 50 μm, 60 μm, etc.
[0100] In one embodiment of the present application, the particle size of the graphene particles is ≤3 μm;
[0101] In one embodiment of the present application, the chemical formula of the lithium manganese iron phosphate particles is LiMn 1-x Fe xPO4, wherein x=0.05-0.95; more preferably, x=0.4-0.6.
[0102] In one embodiment of the present application, the mass ratio of the graphene particles to the carbon nanotubes is 1 / 4 to 7 / 3; for example, it can be 2 / 8, 3 / 7, 4 / 6, 5 / 5, 6 / 4, 7 / 3 or any value between 1 / 4 and 7 / 3. In other words, the mass of the graphene particles is 20% to 70% of the total mass of the graphene particle-carbon nanotube mixture.
[0103] In one embodiment of the present application, the binder includes polyvinylidene fluoride and / or polyacrylate;
[0104] In one embodiment of the present application, the conductive agent includes at least one of graphite, acetylene black, conductive carbon black and conductive fiber.
[0105] In an optional embodiment, the step S2, mixing the multi-element precursor material with graphene particles and carbon nanotubes, further comprises adding an organic solvent;
[0106] In one embodiment of the present application, the method B adopted for the pre-baking treatment further includes adding the organic solvent;
[0107] In one embodiment of the present application, in step S22, if the pre-baking treatment adopts method A, the process of forming the auxiliary material mixture by mixing the conductive agent and the binder also includes adding a solid active material;
[0108] In one embodiment of the present application, in step S22, if the pre-baking treatment adopts method B, the multi-component precursor material is sequentially mixed with the conductive agent and the raw material mixture to prepare a slurry, or the multi-component precursor material, the raw material mixture and the conductive agent are mixed together and prepared into a slurry, and the solid active material is also added;
[0109] In one embodiment of the present application, the solid active material includes at least one of a lithium manganese oxide material, a ternary material, a lithium manganese-rich material, and a lithium iron phosphate material;
[0110] In one embodiment of the present application, the organic solvent includes at least one of N-methyl-2-pyrrolidone, dimethyl carbonate, diethylene carbonate and ethylene carbonate;
[0111] The solid raw materials for preparing the composite slurry include the following components in parts by weight:
[0112] The number of the lithium manganese iron phosphate particles is 20 to 97; for example, it can be 20, 30, 50, 70, 90, 97, etc.
[0113] The binders 1 to 5 may be, for example, 1, 2, 3, 4, 5, and so on.
[0114] The conductive agents 1 to 3 may be, for example, 1, 2, 3, and so on.
[0115] The raw material mixture is 0.5 to 2; for example, it can be 0.5, 1, 1.5, 2, etc.
[0116] Solid active material 0 to 77. For example, it can be 0, 1, 5, 10, 30, 50, 70, 77 and so on.
[0117] For example, in one embodiment, the solid raw materials for preparing lithium iron manganese phosphate composite slurry, calculated by taking the total mass percentage as 100%, include: 20%-97% of lithium iron manganese phosphate particles, 1%-5% of solid binder particles, 1%-3% of solid conductive agent and 0.5%-2% of graphene-carbon nanotube mixture, 0-77.5% of solid active materials such as lithium manganese oxide materials, ternary materials, lithium manganese-rich materials, lithium iron phosphate materials, etc.
[0118] By rationally allocating the amounts of positive electrode active material, conductive agent, and binder in the composite slurry and preparing a slurry with suitable viscosity, the composite slurry can have good dispersibility, stability, coating performance, and adhesion.
[0119] In one embodiment of the present application, the step S21, mixing graphene particles and carbon nanotubes to obtain a raw material mixture, comprises:
[0120] (1) In one embodiment of the present application, the graphene particles are dispersed in the organic solvent to obtain a graphene slurry; the carbon nanotubes are dispersed in the organic solvent to obtain a carbon nanotube slurry; the graphene slurry and the carbon nanotube slurry are mixed to obtain the raw material mixture;
[0121] (2) In another embodiment of the present application, the graphene particles and the carbon nanotubes are dispersed in the solvent to obtain the raw material mixture.
[0122] In the above embodiment, the raw material mixture is prepared by a mixing method in a wet mixing method, including: dispersing graphene particles in a solvent to obtain graphene slurry, dispersing carbon nanotubes in a solvent to obtain carbon nanotube slurry, adding the graphene slurry to the carbon nanotube slurry, stirring evenly, and obtaining a suspension of the raw material mixture; or, directly dispersing the graphene particles and the carbon nanotubes in a solvent to obtain a suspension of the raw material mixture.
[0123] In one embodiment of the present application, in step S22, the conductive agent and the binder are mixed to form an auxiliary material mixture, including:
[0124] Dissolving the binder in the solvent to obtain a glue solution; adding the conductive agent to the glue solution, stirring and mixing, to obtain the auxiliary material mixture;
[0125] The above are steps in the wet mixing method, that is, dissolving the binder in a solvent to obtain a glue solution, adding the conductive agent to the glue solution, stirring evenly, and obtaining a glue solution of the auxiliary material mixture.
[0126] In the step S22, the mixed pulping process includes:
[0127] After the materials are mixed, the overall viscosity of the slurry is adjusted using the organic solvent until the viscosity reaches the coating requirement, thereby obtaining the composite slurry.
[0128] The above method is applied to the mixed slurry treatment in the wet mixing method, including: adding the baked lithium manganese iron phosphate particles and / or solid active materials to the glue of the auxiliary material mixture to obtain an initial slurry, and then using an organic solvent to adjust the overall viscosity of the initial slurry until the viscosity reaches the coating requirements to obtain a lithium manganese iron phosphate composite slurry.
[0129] The above method is applied to the mixed slurry treatment in the semi-dry mixing method, including: using method B for baking pre-treatment to obtain a multi-component precursor material; first mixing the raw materials containing graphene particles and carbon nanotubes to obtain a raw material mixture; adding the multi-component precursor material to the suspension of the raw material mixture to obtain an initial slurry, and then using an organic solvent to adjust the overall viscosity of the initial slurry until the viscosity reaches the coating requirement to obtain a lithium manganese iron phosphate composite slurry.
[0130] It is understandable that, due to the nano-agglomeration characteristics of graphene particles and carbon nanotubes, the mixture of graphene particles and carbon nanotubes can be first dispersed in an organic solvent, and then mixed with a multi-element precursor material in the form of a suspension of the raw material mixture, so that the powder can be easily mixed and stirred evenly with the graphene particles-carbon nanotube mixture in the solvent. Alternatively, the graphene particles and carbon nanotubes can be mixed evenly with other positive electrode materials as much as possible by dry mixing, and then an organic solvent is added and fully stirred. After stirring, a certain amount of organic solvent is further added according to the viscosity state of the composite slurry to adjust the slurry viscosity to ensure that it can be coated on the current collector in the end.
[0131] In one embodiment of the present application, at least one of the following mixing treatments is dry mixing:
[0132] A. In step S22, the pre-baking treatment adopts method B, that is, the multi-element precursor material is sequentially mixed with the conductive agent and the raw material mixture;
[0133] B. In step S22, the pre-baking treatment adopts method B, which is a treatment method of mixing the multi-component precursor material, the raw material mixture and the conductive agent together;
[0134] C. In the method B of the pre-baking treatment in step S1, the lithium manganese iron phosphate particles are mixed with a binder;
[0135] In one embodiment of the present application, the dry mixing processing method is:
[0136] The mixture was stirred in a planetary mixer at a rotation speed of 500 rpm to 1200 rpm and a revolution speed of 10 rpm to 30 rpm for 30 min to 120 min.
[0137] For example, the lithium manganese iron phosphate particles and the binder particles can be placed in a planetary mixer, and then the two particles can be evenly mixed at a rotation speed of 500 rpm and a revolution speed of 30 rpm; or the first mixed powder and the solid conductive agent can be placed in a planetary mixer, and then the solid mixed materials can be evenly mixed at a rotation speed of 1200 rpm and a revolution speed of 10 rpm, which is not specifically limited here. Through this dry mixing method, the solid powders can be dispersed more evenly.
[0138] In addition, a composite slurry is also provided in an embodiment of the present application, which is prepared by the method for preparing the composite slurry described in any of the aforementioned embodiments.
[0139] In addition, an embodiment of the present application further provides a positive electrode sheet, which is prepared by using the composite slurry described in the aforementioned embodiment.
[0140] As described above, the prepared lithium manganese iron phosphate composite slurry is coated on the surface of the current collector, rolled, dried, and then cut to obtain a positive electrode sheet.
[0141] In addition, a battery is provided in an embodiment of the present application, comprising the positive electrode sheet described in the above embodiment.
[0142] As described above, the prepared positive electrode sheet and negative electrode sheet, electrolyte, separator, etc. are assembled to prepare a lithium-ion battery.
[0143] In addition, an embodiment of the present application further provides an electrical device, characterized in that it includes a battery as described in the aforementioned embodiment.
[0144] For example, it may include but is not limited to smart devices, computers, tablets, wearable devices, electric vehicles, etc.
[0145] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0146] Example 1
[0147] This embodiment provides a lithium manganese iron phosphate composite slurry, and its preparation process is as follows: Figure 1 The preparation method of the composite slurry specifically includes:
[0148] (1) 3 kg of polyvinylidene fluoride binder particles (particle size D 50 30 kg of NMP was added to the nanostructured particles (15 μm) for mixing. The mixing method was stirring in a planetary stirring pot at a speed of 500 r / min for dispersion and 20 r / min for stirring. The stirring was continued for 2 h to obtain a glue solution.
[0149] (2) 1.2 kg of conductive carbon black was added to the planetary stirring pot through a nitrogen-protected delivery pipeline, and mixed with the adhesive solution at a stirring speed of 500 r / min for dispersion and 20 r / min for 1 h to obtain a conductive adhesive solution of the auxiliary material mixture.
[0150] (3) Dispersing 1.5 kg of graphene particle-carbon nanotube mixture in NMP solvent (wherein the mass of graphene particles is 0.3 kg, the particle size D50 is 1.8 μm, and the mass of carbon nanotubes is 1.2 kg) to obtain a suspension of the raw material mixture (solid content is 4%), and then adding the suspension of the raw material mixture to the auxiliary material mixture prepared in the planetary stirring pot in step (2), and continuing to stir at the same stirring speed.
[0151] (4) Using the baking pretreatment method A, 94.3 kg of lithium manganese iron phosphate particles (particle size D 50 The particles were heated and baked at 120° C. for 24 h. The moisture content of the lithium manganese iron phosphate particles after baking was tested to be 413 ppm, thereby obtaining a multi-component precursor material.
[0152] (5) The multi-component precursor material baked in step (4) was cooled to 20°C and sealed and packaged. A portion was weighed and transported to a planetary stirring pot through a nitrogen-protected pipeline, and mixed with the mixture therein; the stirring speed was 500 r / min for dispersion, 20 r / min for stirring, and stirred for 2 hours. NMP solvent was then added to adjust the overall viscosity of the composite slurry until the slurry viscosity was 16000 mPas and the solid content was 63.40%, thereby obtaining a composite slurry.
[0153] This embodiment also prepares a positive electrode sheet, and its preparation method includes: coating the composite slurry prepared in step (5) on the carbon-coated aluminum foil, and drying it to prepare the positive electrode sheet.
[0154] This embodiment also prepares a lithium-ion battery, and the prepared positive electrode sheet is sliced, and the negative electrode sheet, solid electrolyte or separator are used for lamination, welding, shell assembly, drying, liquid injection, formation and capacity division to prepare a lithium-ion battery.
[0155] Example 2
[0156] The preparation method of lithium manganese iron phosphate composite slurry provided in this embodiment is the same as that in embodiment 4, except that: the particle size D of the graphene particles in step (3) is 50 is 3μm.
[0157] The preparation method of the positive electrode sheet and lithium ion battery provided in this embodiment is the same as that in embodiment 1.
[0158] Example 3
[0159] The preparation method of lithium manganese iron phosphate composite slurry provided in this embodiment is the same as that in embodiment 4, except that: the particle size D of the graphene particles in step (3) is 50 It is 7.5μm.
[0160] The preparation method of the positive electrode sheet and lithium ion battery provided in this embodiment is the same as that in embodiment 1.
[0161] Example 4
[0162] refer to Figure 2 The preparation method of the lithium manganese iron phosphate composite slurry provided in this embodiment is the same as that in Example 1, except that the masses of the graphene particles and carbon nanotubes in the graphene particle-carbon nanotube mixture in step (3) are 0.6 kg and 0.9 kg respectively, and the other parameters remain unchanged.
[0163] The preparation method of the positive electrode sheet and lithium ion battery provided in this embodiment is the same as that in embodiment 1.
[0164] Example 5
[0165] refer to Figure 3The preparation method of the lithium manganese iron phosphate composite slurry provided in this embodiment is the same as that in Example 1, except that the masses of the graphene particles and carbon nanotubes in the graphene particle-carbon nanotube mixture in step (3) are 1.05 kg and 0.45 kg respectively, and the other parameters remain unchanged.
[0166] The preparation method of the positive electrode sheet and lithium ion battery provided in this embodiment is the same as that in embodiment 1.
[0167] Example 6
[0168] The method for preparing the lithium manganese iron phosphate composite slurry provided in this embodiment includes:
[0169] (1) 94.3 kg of lithium manganese iron phosphate particles (D50 of 1.5 μm) and 3 kg of polyvinylidene fluoride binder particles (D50 of 15 μm) were mixed in a planetary stirring pot at a stirring speed of 500 r / min for dispersion and 20 r / min for stirring for 30 min to obtain a first mixed powder;
[0170] (2) heating and baking the first mixed powder of step (1) at a temperature of 120° C. for 24 h, and testing the moisture contents of the lithium manganese iron phosphate particles and the binder particles after baking, which were 478 ppm and 311 ppm, respectively;
[0171] (3) cooling the first mixed powder baked in step (2) to 20° C. and sealing and packaging it, weighing a portion and then transporting it to a planetary stirring pot through a nitrogen-protected pipeline;
[0172] (4) adding 1.2 kg of conductive carbon black to the planetary stirring pot through a nitrogen-protected delivery pipeline, and mixing and stirring with the first mixed powder, with a stirring speed of 500 r / min for dispersion and 20 r / min for stirring for 15 min to obtain a second mixed powder;
[0173] (5) 1.5 kg of graphene particle-carbon nanotube mixture was dispersed in NMP solvent (wherein the mass of graphene particles was 0.3 kg, the particle size D50 was 1.8 μm, and the mass of carbon nanotubes was 1.2 kg) to obtain a raw material mixture (solid content was 4%), and the suspension of the raw material mixture was added to a planetary stirring pot containing the second mixed powder at a flow rate of 5 L / min for slurrying. The stirring speed was 20 r / min for stirring and 300 r / min for dispersing. After all the suspension was added, stirring was continued for 1 hour, and NMP solvent was added to adjust the overall viscosity of the composite slurry until the slurry viscosity was 16000 mPas and the solid content was 63.95%.
[0174] The preparation method of the positive electrode sheet and lithium ion battery provided in this embodiment is the same as that in embodiment 1.
[0175] Example 7
[0176] The method for preparing the lithium manganese iron phosphate composite slurry provided in this embodiment includes:
[0177] (1) 94.3 kg of lithium manganese iron phosphate particles (D 50 1.5 μm) and 3 kg of polyvinylidene fluoride binder particles (D50 is 15 μm) are mixed in a planetary stirring pot at a stirring speed of 500 r / min for dispersion, 20 r / min for stirring, and stirring for 30 min to obtain a first mixed powder;
[0178] (2) heating and baking the first mixed powder of step (1) at a temperature of 120° C. for 24 h, and testing the moisture contents of the lithium manganese iron phosphate particles and the binder particles after baking, which were 403 ppm and 352 ppm, respectively;
[0179] (3) cooling the first mixed powder baked in step (2) to 20° C. and sealing and packaging it, weighing a portion and then transporting it to a planetary stirring pot through a nitrogen-protected pipeline;
[0180] (4) 1.2 kg of conductive carbon black, 0.3 kg of graphene particles (particle size D50 is 3 μm), and 1.2 kg of carbon nanotubes are further added to the planetary stirring pot through a nitrogen-protected delivery pipeline, and mixed with the first mixed powder for stirring at a stirring speed of 500 r / min for dispersion and 20 r / min for stirring for 15 min to obtain a third mixed powder;
[0181] (5) Adding NMP solvent to the third mixed powder to adjust the overall viscosity of the composite slurry until the slurry viscosity is 16000 mPas and the solid content is 63.67%.
[0182] The preparation method of the positive electrode sheet and lithium ion battery provided in this embodiment is the same as that in embodiment 1.
[0183] Comparative Example 1
[0184] The preparation method of the lithium iron manganese phosphate composite slurry provided in this comparative example is the same as that in Example 1, except that: there is no heating and baking process in step (4) and no cooling process in step (5).
[0185] Comparative Example 2
[0186] The preparation method of the lithium manganese iron phosphate composite slurry provided in this comparative example is the same as that in Example 1, except that no graphene particles are added. That is, step (3) is to disperse 1.5 kg of carbon nanotubes in NMP solvent to obtain a raw material mixture (solid content is 4%), and then add the suspension of the raw material mixture to the first conductive glue prepared in the planetary stirring pot in step (2), and continue to stir at the same stirring speed to obtain a second conductive glue.
[0187] Comparative Example 3
[0188] The preparation method of the lithium manganese iron phosphate composite slurry provided in this comparative example is the same as that in Example 1, except that: the particle size D of the graphene particles in step (3) is 50 8μm.
[0189] Comparative Example 4
[0190] The preparation method of the lithium iron manganese phosphate composite slurry provided in this comparative example is the same as that in Example 1, except that the masses of the graphene particles and carbon nanotubes in the graphene particle-carbon nanotube mixture in step (3) are 1.2 kg and 0.3 kg respectively, and the other parts remain unchanged.
[0191] Comparative Example 5
[0192] The preparation method of the lithium iron manganese phosphate composite slurry provided in this comparative example is the same as that in Example 6, except that: there is no heating and baking process in step (2) and no cooling process in step (3).
[0193] Comparative Example 6
[0194] The preparation method of the lithium iron manganese phosphate composite slurry provided in this comparative example is the same as that in Example 7, except that: there is no heating and baking process in step (2) and no cooling process in step (3).
[0195] Comparative Example 7
[0196] The preparation method of the lithium iron manganese phosphate composite slurry provided in this comparative example is the same as that in Example 1, the difference is that only graphene particles are added to the mixture of graphene particles and carbon nanotubes, and no carbon nanotube particles are added.
[0197] Horizontal comparison experiment:
[0198] The lithium ion batteries prepared in the above embodiments and comparative examples were tested, and the capacity was tested for 300 charge and discharge cycles at 0.5C rate at 45°C, and 0.5C discharge, with a voltage window of 2.7V-4.2V, and the capacity was calculated and the capacity retention rate was obtained as follows: Figure 4 The cycle performance test results are shown.
[0199] The viscosity test of the slurry obtained in the above embodiments and comparative examples was carried out by using the NDJ-8S rotational viscometer produced by Shanghai Xinnuo Instruments, and the test rotor and speed were 12 rpm for rotor No. 6. The solid content test method of the slurry after viscosity adjustment is to take a sample of 0.2 g, prepare a wet film, bake it at 200°C for 30 minutes, and test the weight change before and after the test, and the solid content of the slurry. The prepared positive electrode sheet was tested for surface resistance. The test equipment was the electrode sheet resistance meter BER2500 produced by Xiamen Yuanneng Technology. The test pressure was 35 MPa and the holding time was 15 s. The prepared battery was subjected to a cycle performance test. The test equipment was the BTS-5V100A32CH battery test system produced by Shenzhen Shenghong Electric. The cycle conditions were 45°C, 0.5C rate charge and discharge, and a voltage range of 2.7V to 4.2V. The test results are shown in Table 1.
[0200] Table 1. Test results of various embodiments and comparative examples
[0201] example Solid content Resistivity Capacity retention rate 1 63.81% 24.26 90.67 2 61.72% 12.97 90.21 3 63.11% 27.49 91.20 4 64.84% 29.03 91.20 5 63.48% 25.54 91.19 6 62.59% 26.38 91.73 7 65.55% 37.66 90.20 Real 1 64.17% 25.07 95.00 Real 2 64.99% 25.63 94.80 Reality 3 63.27% 26.28 91.21 Reality 4 65.25% 27.79 92.01 Reality 5 65.15% 31.66 92.01 Actual 6 64.07% 25.90 94.97 Real 7 64.26% 26.18 94.98
[0202] In the above table, "Comparative Example" represents a comparative example, such as "Comparative Example 1" is Comparative Example 1; similarly, "Example" represents an embodiment, such as Example 1 is Example 1; solid content represents the solid content of the slurry at 16000 mPa·s; resistivity represents the electrode resistivity at 35 MPa (Ω*cm); capacity retention rate represents the capacity retention rate (%) after 300 charge and discharge cycles at 45°C and 0.5C.
[0203] The data in Table 1 provide the test results of solid content, resistivity and capacity retention rate of lithium-ion battery slurries prepared in different embodiments and comparative examples. It can be seen from the data that:
[0204] Solid content: Solid content refers to the percentage of solid components in the slurry. The higher the solid content, the more active substances are contained in the slurry, which may increase the energy density of the battery. As can be seen from the table, the solid content ranges from 61.72% to 65.55%, among which Comparative Example 7 has the highest solid content and Example 5 has the lowest solid content.
[0205] Resistivity: Resistivity is an indicator of the conductivity of a material. The lower the resistivity, the better the conductivity of the material. From the data in the table, it can be seen that the resistivity of Comparative Example 2 is the lowest, which is 12.97, and the resistivity of Comparative Example 7 is the highest, which is 37.66. The resistivity of the embodiments is generally lower than that of the comparative examples, which indicates that the composite slurry in the embodiments may have better conductivity.
[0206] Capacity retention rate: The capacity retention rate refers to the ratio of the remaining capacity to the initial capacity after a certain number of charge and discharge cycles. The higher this ratio is, the better the cycle performance of the battery is and the slower the capacity decay is. It can be seen from the data in the table that the capacity retention rate of the embodiments is generally higher than that of the comparative examples, among which the capacity retention rate of embodiment 5 is the highest, which is 92.01%, and the capacity retention rate of comparative example 2 is the lowest, which is 90.21%.
[0207] From these data, the following conclusions can be drawn:
[0208] (1) The composite slurry in the embodiment has better conductivity (lower resistivity) and cycle performance (higher capacity retention rate) than the comparative example.
[0209] (2) Pre-baking treatment and addition of graphene particles have a positive effect on improving battery performance, which can be seen from the data comparison between the embodiment and the comparative example.
[0210] (3) The particle size and mass ratio of graphene particles have a certain influence on battery performance. Different embodiments optimize battery performance by adjusting these parameters.
[0211] In summary, in the preparation method of lithium manganese iron phosphate composite slurry provided in the present application, when the solid raw materials are mixed, a baking pre-treatment is first performed, which can achieve moisture control in advance and improve the water absorption rate problem; the use of graphene particles and carbon nanotubes can make the solid particles in the composite slurry evenly dispersed. Among them, in addition to being a conductive agent in the slurry preparation process, the graphene particles have a particle size D 50 It is 1.2 to 5 times the D50 particle size of lithium manganese iron phosphate particles. In addition, the graphene structure has the effects of lubrication, isolation and hydrophobicity on local lithium manganese iron phosphate particles, and achieves significant improvements in the dispersion and fluidity of the slurry through steric hindrance, thereby optimizing the quality of porous electrode film formation and improving the battery's cycle performance.
[0212] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a composite slurry, characterized in that: include: S1, performing a pre-baking treatment on lithium iron manganese phosphate particles to obtain a multi-element precursor material; S2, mixing the multi-element precursor material with graphene particles and carbon nanotubes to prepare a composite slurry; Wherein, the particle size D of the graphene particles 50 is the particle size D of the lithium manganese iron phosphate particles 50 1.2 to 5 times of.
2. The method for preparing the composite slurry according to claim 1, characterized in that: The pre-baking treatment in step S1 includes at least one of the following methods: Method A: directly baking the lithium manganese iron phosphate particles to obtain the multi-element precursor material; Method B: mixing the lithium manganese iron phosphate particles with a binder, and then baking to obtain the multi-element precursor material; Preferably, the baking comprises: raising the temperature to a heat treatment temperature under a protective gas atmosphere, and continuing the baking for 4 hours to 36 hours; Preferably, after the baking, the moisture content in the multi-component precursor material is less than 1500 ppm; Preferably, the heat treatment temperature is lower than the thermal decomposition temperature of the binder; Preferably, the heat treatment temperature is ≥88°C; Preferably, the protective gas includes at least one of nitrogen, helium and hydrogen; Preferably, the step S2 comprises: S21, mixing graphene particles and carbon nanotubes to obtain a raw material mixture; S22, if the pre-baking treatment adopts method A, a conductive agent and a binder are mixed to form an auxiliary material mixture, and the multi-component precursor material and the auxiliary material mixture are mixed and slurried to obtain the composite slurry; If the pre-baking treatment adopts method B, the multi-component precursor material is sequentially mixed with the conductive agent and the raw material mixture, and mixed and slurried together, or the multi-component precursor material, the raw material mixture and the conductive agent are mixed and slurried together to obtain the composite slurry; Preferably, the particle size D of the lithium manganese iron phosphate particles is 50 0.3μm~5μm; Preferably, the diameter of the carbon nanotube is ≤50nm; Preferably, the carbon nanotube has a tube length of ≤100 μm; Preferably, the particle size D50 of the binder is 0.1 μm to 60 μm; Preferably, the particle size of the graphene particles is ≤3 μm; Preferably, the chemical formula of the lithium iron manganese phosphate particles is LiMn 1-x Fe x PO4, where x = 0.05 to 0.95; Preferably, the mass ratio of the graphene particles to the carbon nanotubes is 1 / 4 to 7 / 3; Preferably, the binder comprises polyvinylidene fluoride and / or polyacrylate; Preferably, the conductive agent includes at least one of graphite, acetylene black, conductive carbon black and conductive fiber.
3. The method for preparing the composite slurry according to claim 2, characterized in that: The step S2, mixing the multi-element precursor material with graphene particles and carbon nanotubes, also includes adding an organic solvent; And / or, the method B adopted for the pre-baking treatment further comprises adding the organic solvent; And / or, in step S22, if the pre-baking treatment adopts method A, the process of forming the auxiliary material mixture by mixing the conductive agent and the binder also includes adding a solid active material; And / or, in step S22, if the pre-baking treatment adopts method B, the multi-component precursor material is sequentially mixed with the conductive agent and the raw material mixture to prepare a slurry, or the multi-component precursor material, the raw material mixture and the conductive agent are mixed together and the slurry is prepared, and the solid active material is also added; Preferably, the solid active material includes at least one of a lithium manganese oxide material, a ternary material, a lithium manganese-rich material and a lithium iron phosphate material; Preferably, the organic solvent comprises at least one of N-methyl-2-pyrrolidone, dimethyl carbonate, diethylene carbonate and ethylene carbonate; The solid raw materials for preparing the composite slurry include the following components in parts by weight: The lithium manganese iron phosphate particles are 20 to 97; The binders 1 to 5; The conductive agents 1 to 3; Raw material mixture 0.5~2; Solid active material 0~77.
4. The method for preparing the composite slurry according to claim 3, characterized in that: The step S21, mixing graphene particles and carbon nanotubes to obtain a raw material mixture, comprises: Dispersing the graphene particles in the organic solvent to obtain graphene slurry; dispersing the carbon nanotubes in the organic solvent to obtain carbon nanotube slurry; mixing the graphene slurry and the carbon nanotube slurry to obtain the raw material mixture; Alternatively, the graphene particles and the carbon nanotubes are dispersed in the solvent to obtain the raw material mixture.
5. The method for preparing the composite slurry according to claim 3, characterized in that: In the step S22, the conductive agent and the binder are mixed to form an auxiliary material mixture, including: Dissolving the binder in the solvent to obtain a glue solution; adding the conductive agent to the glue solution, stirring and mixing, to obtain the auxiliary material mixture; In the step S22, the mixed pulping process includes: After the materials are mixed, the overall viscosity of the slurry is adjusted using the organic solvent until the viscosity reaches the coating requirement, thereby obtaining the composite slurry.
6. The preparation method according to claim 3, characterized in that: At least one of the following mixing methods is dry mixing: A. In step S22, the pre-baking treatment adopts method B, that is, the multi-element precursor material is sequentially mixed with the conductive agent and the raw material mixture; B. In step S22, the pre-baking treatment adopts method B, which is a treatment method of mixing the multi-component precursor material, the raw material mixture and the conductive agent together; C. In the method B of the pre-baking treatment in step S1, the lithium manganese iron phosphate particles are mixed with a binder; Preferably, the dry mixing process is: The mixture was stirred in a planetary mixer at a rotation speed of 500 rpm to 1200 rpm and a revolution speed of 10 rpm to 30 rpm for 30 min to 120 min.
7. A composite slurry, characterized in that: The composite slurry is prepared by the method for preparing the composite slurry according to any one of claims 1 to 6.
8. A positive electrode sheet, characterized in that: The positive electrode sheet is prepared using the composite slurry described in claim 7.
9. A battery, characterized in that: Including the positive electrode sheet as claimed in claim 8.
10. An electrical equipment, characterized in that: Comprising the battery as claimed in claim 9.